Psychological Examination of Political Philosophies: Interrelationship Among Citizenship, Justice, and Well-Being in Japan - Kobayashi, Masaya (Frontiers in Psychology, 2022)
This paper examines assumptions concerning the relationship between citizenship, justice, and well-being, based on representative political philosophies, including egoism, utilitarianism, libertarianism, liberalism, and communitarianism. A previous paper raised the possibility of an inter-disciplinary framework for collaboration between psychology and political philosophy. This study picks up that thread and attempts to actualize a collaborative research effort based on a framework grounded in positive political psychology. The first part of this study reflects on the methodology situated between empirical psychology and philosophy in reference to the debates caused by psychological and philosophical situationism. In response to its criticism against virtue ethics, the possibility of reconstructing it on empirical psychology has paradoxically emerged. Similarly, this study validates assumptions on political philosophies employing the psychological method concerning well-being. Accordingly, the central part examines the plausibility of the assumptions by empirical evidence obtained from two internet surveys (2020, N5000; 2021, N6885) in Japan. The relationships between citizenship, justice, and well-being are the most substantial in the communitarian assumption. The exploratory factor analysis of the two surveys illuminates that the correlations between citizenship, justice, and well-being (or political well-being) are substantial. This relationship denies the egoism assumption. Moreover, almost all correlations between the three are higher based on virtue-related indicators than hedonic ones. These findings are not in tune with the utilitarian assumption and are most congruent to the communitarian assumption. In addition, citizenship and justice correlate more with political well-being than overall well-being. As these are more directly associated with political well-being in the communitarian assumption, this result aligns with the assumption. Furthermore, the positive relationship between disparity elimination and well-being fits the liberal rather than the libertarian assumption. Nevertheless, the substantial correlation between ethical justice and well-being is higher by virtue-related indicators than hedonic indicators, suggesting distributive justice is associated with the ethical dimension. Again, this fits the communitarian assumption rather than the liberal assumption. Thus, philosophical psychology empirically verifies the interdependence of the three conceptions and the relative plausibility of the communitarian assumption. Moreover, as the relationship between the three is essential for political philosophies, the result increases the reliability of communitarianism.